Health self-esteem of 55 years and older Muscovites, traditional risk factors and their prognostic value - S. A. Shalnova; A. E. Imaeva; A. V. Kapustina; G. A. Muromtseva; Yu. A. Balanova; V. M. Shkolnikov (Российский кардиологический журнал, 2019)
Health self-esteem is an integral parameter that reflects a person’s subjective feelings about their health and is widely used in health research. Under the tendency of population aging, health self-esteem to determine the life prognosis of the elderly is needed.Aim. To study the role of health self-esteem in all-cause and cardiovascular disease (CVD) mortality among 55 years and older Muscovites.Material and methods. A cohort, prospective study was conducted on a sample of 55 years and older Muscovites. The analysis included data of 1876 people, including 898 men. A standard questionnaire, that included socio-demographic data, anamnesis, behavioral habits was used. Anthropometric data, blood pressure, cholesterol levels and a highly sensitive C-reactive protein (hsCRP) were determined. Health self-esteem were defined as poor, satisfactory and good. Statistical analysis was performed using the STATA 14.0 statistical package.Results. Only 10% of Muscovites aged 55 years and older rated their health as good. The prevalence of poor health self-esteem was 18,6%. Moreover, with age, bad health self-esteem increased not only due to “good health” decrease, but also due to a decrease in the frequency of satisfactory health self-esteem. Health self-esteem were significantly more frequently reported in women and those with low levels of education. When conducting multivariate analysis, arterial hypertension, smoking, increased hsCRP, glycated hemoglobin and obesity were significantly associated with poor health self-esteem. At the same time, an analysis of mortality has shown that poor health self-esteem is an independent predictor of death in the elderly, even with CVD, smoking and other risk factors.Conclusion. Health self-esteem is an indicator independently and reliably associated with mortality. This suggests that health self-esteem may be useful in practice as a routinely measured indicator for screening the elderly population for making preventive interventions.